Integrated Digital Module Learning Management System (LMS) Development in Microbiological Practices - Nurrijal (Edutechnium Journal of Educational Technology, 2023)
Digital modules are virtual learning environments as learning media that encourage learners to innovate and put learning content that can be obtained anywhere and anytime through digital learning. This development aims to design and develop digital modules that are a source of learning media for students to carry out digital practicum (PRAKTAL), integrated with the Learning Management System (LMS) in Microbiology course with a blended learning strategy. The development of this digital module goes through the Analysis, Design, Development, Implementation, Evaluation stages. The product results have been declared valid and feasible with the criteria, 98.13% of material experts, 96.74% of media experts, and 97.00% of education practitioners. The trial implementation resulted in 93.06% individual criteria, 92.64% small group trials, and 98.10% classical trials. Learning media shows effectiveness with an indication of the students' learning success rate, an average of 96.00%.